Kontribusi Praktek Kewirausahaan Santri dalam Penjualan Jamu Mustika Herbal: Study Kasus : Pondok Pesantren Dzikrul Ghofilin Al-Hasyimiyyah Kec. Balapulang Kab. Tegal - Anita Marya; Ifrizah Ifrizah (Jurnal Kewirausahaan Cerdas dan Digital, 2024)
This research aims to understand the contribution of the Dzikrul Ghofilin Al-Hasyimiyysh Islamic Boarding School in developing the entrepreneurial spirit of its students, with the ultimate goal of creating alumni with high entrepreneurial abilities. Using descriptive qualitative methodology and field research, this study collected data through in-depth interviews and observations, supported by relevant documentation. The data analysis process involved in-depth interviews to obtain real results and literature reviews containing conclusions and thoughts from the author from several reference sources obtained. The findings show that Islamic Boarding Schools have a significant role in developing the entrepreneurial spirit among students, especially through the implementation of strict financial independence, such as understanding the importance of business. It is hoped that students will leave the Islamic boarding school with strong entrepreneurial knowledge and awareness of opportunities, both in the online and offline world of work, as well as the ability to create new jobs.